2007
DOI: 10.1038/sj.npp.1301315
|View full text |Cite
|
Sign up to set email alerts
|

Atomoxetine Reverses Nicotine Withdrawal-Associated Deficits in Contextual Fear Conditioning

Abstract: Recent evidence suggests that the cognitive symptoms of nicotine withdrawal and the cognitive symptoms of attention deficit hyperactivity disorder (ADHD) may share neural correlates. Thus, therapeutics that ameliorate ADHD symptoms may also ameliorate nicotine-withdrawal symptoms. The present research tested this hypothesis in an animal model of nicotine withdrawal-associated cognitive deficits using atomoxetine, a norepinephrine reuptake inhibitor that is approved by the FDA to treat the symptoms of ADHD. C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 78 publications
1
49
0
Order By: Relevance
“…It is important to note that these plasma nicotine levels were within the range observed in smokers [5,64]. Additionally, withdrawal from chronic nicotine disrupts contextual but not cued conditioning [2,33,30,132,133], and this impairment in contextual learning can be ameliorated by nicotine replacement and by the smoking cessation drugs bupropion and varenicline [30,132,135]. Together, these data suggest that associations between stimuli and the effects of nicotine in humans may contribute to nicotine addiction, and these effects can be modeled in mice by studying the effects of nicotine on contextual learning.…”
Section: Nicotinic Acetylcholine Receptors: Animal Researchmentioning
confidence: 61%
See 2 more Smart Citations
“…It is important to note that these plasma nicotine levels were within the range observed in smokers [5,64]. Additionally, withdrawal from chronic nicotine disrupts contextual but not cued conditioning [2,33,30,132,133], and this impairment in contextual learning can be ameliorated by nicotine replacement and by the smoking cessation drugs bupropion and varenicline [30,132,135]. Together, these data suggest that associations between stimuli and the effects of nicotine in humans may contribute to nicotine addiction, and these effects can be modeled in mice by studying the effects of nicotine on contextual learning.…”
Section: Nicotinic Acetylcholine Receptors: Animal Researchmentioning
confidence: 61%
“…Mice withdrawn from nicotine spend less time on the open arms relative to saline controls, indicating increased anxiety [28,77]. Furthermore, nicotine withdrawal-related deficits in contextual learning have been evaluated in mice [33,30,132,133]. Withdrawal-related decreases in the brain reward system in humans has been modeled using the intracranial self stimulation (ICSS) procedure, in which rats press a lever to deliver electrical stimulation to reward-related brain areas.…”
Section: Nicotinic Acetylcholine Receptors: Animal Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Osmotic pumps (Alzet, Durect Coporation, Cupertino, CA) were used to continuously infuse 0.9% NaCl vehicle or nicotine (Sigma-Aldrich, Tokyo, Japan) at a dose of 12 mg/kg/day of free base (32.4 mg/kg/day nicotine salt, pH corrected to 7.2 ± 0.2 using 1M NaOH) [35,36].…”
Section: Drugsmentioning
confidence: 99%
“…An intermediate nicotine dose (12 mg/kg/day) was employed based on previous studies in which termination of 6.3 -24 mg/kg/day nicotine produced an abstinence syndrome in terms of physical withdrawal, contextual fear responses and anxiety-like behaviors [35,36,67,68].Thus, taste reactivity may simply be unable to, or be insufficient to detect an affective mg/kg/day of nicotine [69], however, another study reported a dose of 40 mg/kg over 28 days was needed to produce changes in ICSS thresholds [70]. Furthermore, motivational impairment as measured by ICSS is precipitated at lower doses of a nicotinic antagonist than somatic signs of withdrawal [54,70].…”
Section: Effect Of Nicotine Withdrawalmentioning
confidence: 99%